Development of white matter in young adulthood: The speed of brain aging and its relationship with changes in fractional anisotropy - Jáni, Martin; Mareček, Radek; Mareckova, Klara (NeuroImage, 2024)
White matter (WM) development has been studied extensively, but most studies used cross-sectional data, and to the best of our knowledge, none of them considered the possible effects of biological (vs. chronological) age. Therefore, we conducted a longitudinal multimodal study of WM development and studied changes in fractional anisotropy (FA) in the different WM tracts and their relationship with cortical thickness-based measures of brain aging in young adulthood. A total of 105 participants from the European Longitudinal Study of Pregnancy and Childhood (ELSPAC) prenatal birth cohort underwent magnetic resonance imaging (MRI) at the age of 23-24, and the age of 28-30 years. At both time points, FA in the different WM tracts was extracted using the JHU atlas, and brain age gap estimate (BrainAGE) was calculated using the Neuroanatomical Age Prediction using R (NAPR) model based on cortical thickness maps. Changes in FA and the speed of cortical brain aging were calculated as the difference between the respective variables in the late vs. early 20s. We demonstrated tract-specific increases as well as decreases in FA, which indicate that the WM microstructure continues to develop in the third decade of life. Moreover, the significant interaction between the speed of cortical brain aging, tract, and sex on mean FA revealed that a greater speed of cortical brain aging in young adulthood predicted greater decreases in FA in the bilateral cingulum and left superior longitudinal fasciculus in young adult men. Overall, these changes in FA in the WM tracts in young adulthood point out the protracted development of WM microstructure, particularly in men.
Keywords: dospělí; Superior longitudinal fasciculus; zobrazování difuzních tenzorů; Female; Adult; mladý dospělý; ženské pohlaví; Sex differences; Aging; longitudinální studie; White Matter; Anisotropy; lidé; mozek; White matter development; Male; Brain aging; Brain; Fractional anisotropy; anizotropie; Young Adult; Diffusion Tensor Imaging; stárnutí; mužské pohlaví; bílá hmota; Longitudinal Studies; Cingulum; Humans